Design and Construction of Knowledge Management System for Teachers' Teaching Materials at SMA 22 Palembang - Muhammad Adlyn Alfarabi; Leon A. Abdillah (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2024)
Improving teacher competence to be better and more honed can be built by sharing knowledge. However, in its implementation, sharing knowledge can be a problem because the knowledge that is disseminated has not been distributed perfectly and irregularly. This happens because there is no container that can accommodate the desired knowledge from research results, teaching materials and teacher teaching methods. Therefore, this study aimed to develop a KMS, designed to efficiently collect, manage, and distribute knowledge. This study was conducted within the scope of State Senior High School (SMA) 22 Palembang City. The creation of this knowledge was carried out in a Nonaka manner, namely Socialization, Combination, and Internalization (SECI). The system development methodology used is the Knowledge Management System Life Cycle (KMSLC), with Unified Modeling Language (UML) modeling to build a website. This study aims to build KMS teaching materials to help teachers in teaching and make it easier for students to obtain knowledge tacitly and explicitly. This study aims to create equality of knowledge between teachers in schools, thus a container is needed that will accommodate this knowledge. Knowledge can be obtained and created through tacit and explicit means, so that students taught by teachers can also know the same knowledge. Therefore, a form is created to discuss with fellow teachers in this system, so that a process of sharing knowledge occurs.